Efficacy of Hijamat Bila Shurt (Dry Cupping) on Intensity of Pain in Dysmenorrhoea- A Preliminary Study - Sultana, A.; Rahman, K.U.; Farzana, M.U.Z.N.; Lone, A. (Ancient Science of Life, 2010)
Waje rehm (Dysmenorrhoea) means painful menstruation. Since ancient times, hijamat bila shurt (Dry cupping) is a method of treatment of for this disease. Therefore, objective of this preliminary study was to evaluate the efficacy of hijamat bila shurt on intensity of pain in waje rehm by using Visual Analogue Scale for pain. It was conducted from May 2009 to July 2010 on 25 patients in National Institute of Unani Medicine, Bangalore. Patients suffering from primary and secondary dysmenorrhoea with regular cycles, age group 12-37years were selected. For dry cupping, two glass cup of medium size were applied below the umbilicus for 15 minutes on day land/or day 2 of the menstrual phase for one cycle and pain intensity was assessed by Visual Analogue Scale score for pain before and after the treatment. The Mean and Standard Error Mean for pain intensity before and after the treatment was 6.48 (0.32) and 2.12 (0.32) respectively with P<0.001, considered significant. Thus, hijamat bila shurt was effective in reducing pain intensity in dysmenorrhoea
Keywords: Hijamat bila shurt; Unani System of Medicine; dry cupping; dysmenorrhoea; visual analogue scale for pain